The bioimpedance phase angle predicts low muscle strength, impaired quality of life, and increased mortality in old patients with cancer - Norman, Kristina; Wirth, Rainer; Neubauer, Maxi; Eckardt, Rahel; Stobaeus, Nicole (Journal of the American Medical Directors Association, 2015)
We investigated the impact of low phase angle (PhA) values on muscle strength, quality of life, symptom severity, and 1-year mortality in older cancer patients.Prospective study with 1-year follow-up.Cancer patients aged >60 years.PhA was derived from whole body impedance analysis. The fifth percentile of age-, sex-, and body mass index-stratified reference values were used as cut-off. Quality of life was determined with the European Organization of Research and Treatment in Cancer questionnaire, reflecting both several function scales and symptom severity. Muscle strength was assessed by hand grip strength, knee extension strength, and peak expiratory flow.433 cancer patients, aged 60-95 years, were recruited. Patients with low PhA (n = 197) exhibited decreased muscle strength compared with patients with normal PhA (hand grip strength: 22 ± 8.6 vs 28.9 ± 8.9 kg, knee extension strength: 20.8 ± 11.8 vs 28.1 ± 14.9 kg, and peak expiratory flow: 301.1 ± 118 vs 401.7 ± 142.6 L/min, P < .001). Physical function, global health status, and role function from the European Organization of Research and Treatment in Cancer questionnaire were reduced, and most symptoms (fatigue, anorexia, pain, and dyspnea) increased in patients with low PhA (P < .001). In a risk-factor adjusted regression analysis, PhA emerged as independent predictor of physical function (ß:-0.538, P = .023), hand grip strength (ß:-4.684, P < .0001), knee extension strength (ß:-4.548, P = .035), and peak expiratory flow (ß:-66.836, P < .0001). Low PhA moreover predicted 1-year mortality in the Cox proportional hazards regression model, whereas grip strength was no longer significant.PhA below the fifth reference percentile is highly predictive of decreased muscle strength, impaired quality of life, and increased mortality in old patients with cancer and should be evaluated in routine assessment.
EVALuna2:10584